استراتيجية جديدة لتنمية مهارات اللغة العربية: دراسة مقارنة بين الجامعة الإسلامية العالمية بماليزيا والجامعات الصينية (Innovative Strategy for the Development of Arabic Language Skills: A Comparative Study between International Islamic University Malaysia) - ما تشنغ بين الصيني, يونس عبد الله (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
الملخّص يهدف هذا البحث إلى تنمية مهارت اللغة العربية بين طلاب جامعات ماليزيا من خلال مقارنة مناهج دراسة اللغة العربية في شعبة التخصص في اللغة العربية التابعة لمركز الدراسات الأساسية بالجامعة الإسلامية العالمية بماليزيا، مقارنا بالمنهج الجامعي لتعليم اللغة العربية، وتنمية مهاراتها في الجامعات الصينية. وقد حاول الباحث من خلال هذا البحث للتعرف لما تتميز به الجامعات الصينية في تمكين طلابها في اللغة العربية، وتنمية مهاراتها بالرغم من غرابة اللغة العربية لهم في حروفها ونطقها وأساليب تراكيبها، كما يحاول معرفة دواعي ضعف مستوى طلابنا في الجامعات الماليزية في اللغة العربية، وفي تنمية مهاراتها بالرغم من كون هذه اللغة مألوفة لديهم منذ صغرهم؛ لكونها لغة القرآن، وكونهم يتعلمون حروفها، وكلماتها لمعايشة القرآن وتلاوته يوميا. والبحث يعتمد على المناهج الوصفية، والتحليلية والمقارنة في عرض المسائل ومناقشة القضايا. ومن أهم ما توصل إليه الباحث من خلال هذا البحث معرفة عظمة اللغة العربية، وقوة مهاراتها الأدائية المتنوعة، وعطائها المتجدد، وتفاعلها مع من يخلص لها كلما تجتمع دواعي اقتناء هذه اللغة من محبة، ورغبة، وحسن منهج، وجهود متواصلة لدى الطلبة والأساتذة والإدارة كما تشهد بذلك جامعات الصين المعاصرة. الكلمات المفتاحيّة: اللغة العربية، جامعات ماليزيا، جامعات صينية، استراتيجية جديدة، تنمية مهارات. Abstract This research aims to develop Arabic language skills for the students of Malaysian universities while comparing the Arabic language curricula used in the Centre for Fundamental Studies (CFS) at the International Islamic University Malaysia and the curricula used at Chinese universities. The researcher surveys the major characteristics that facilitated the students in Chinese universities to master Arabic language skills, despite complexities in Arabic language in terms of its alphabets, pronunciation, and paraphrasing methods. On the other hand, the researcher highlights the reasons behind Malaysian students’ incompetence in Arabic and low level proficiency, notwithstanding their familiarity with the language since their childhood as they learn the Arabic alphabets for recitation of the Qur’an on a daily basis. For the discussion and analysis of the issues in the current study, the researcher has employed descriptive, analytical and comparative methods. This research discerns the greatness of the Arabic language, the strength of its various performance skills, its new contributions, interaction with those who are committed to acquire this language, and who come together in love for, and desire to learn Arabic, good approach and continuous efforts by the students, teachers and the management; these characteristics are prevalent in contemporary Chinese universities. Keywords: Arabic Language, Malaysian Universities, Chinese Universities, Innovative Strategies, Skill Enhancement.